Antidiabetic potential of leaf extracts of Ecobolium linneanum Kurz in streptozotocin-induced diabetic rats - Srilakshmi Nallapaty; Narender Malothu; Rajeswari Pasupula; Alekhya Ketha (GarVal Editorial Ltda., 2022)
Context: In a general context, the importance's of several medicinal plants has been explored in treating diabetes mellitus. In this connection, the antidiabetic potentiality needs to be established for one of the medicinally emerging plants Ecbolium linneanum Kurz. Aims: To evaluate the antidiabetic activity of petroleum ether, ethyl acetate, and methanol extracts of E. linneanum leaves in streptozotocin-induced diabetic rats. Methods: Diabetes was induced by intraperitoneal injection of streptozotocin (60 mg/kg BW) in male Wistar rats. Diabetic rats were treated orally with petroleum ether, ethyl acetate and methanol extracts of E. linneanum leaves at two doses (100 and 200 mg/kg BW/day) for 14 days. The blood glucose, lipid profile, serum enzyme levels, glycosylated haemoglobin (HbA1c), creatinine and serum urea levels were monitored. Glibenclamide (10 mg/kg BW) was used as a standard hypoglycaemic drug. Results: The methanolic leaf extract at 200 mg/kg BW showed increasingly substantial (p<0.001) antidiabetic activity on day 14 and also significantly reduced (p<0.001) SGOT, SGPT, TG, TC, VLDL, LDL, HbA1c and antioxidant enzymes (SOD, CAT and GSH levels) increased significantly (p<0.001) compared to diabetic group. Renal parameters also decreased significantly (p<0.001) at both doses relative to diabetic control, but petroleum leaf extract and ethyl acetate leaf extract exhibited a less significant effect (p<0.05) compared to the methanol extract. All the extracts of leaves showed a protective effect on the oxidative status of the liver at tested concentrations (100 and 200 mg/kg BW). Conclusions: The present research findings revealed that E. linneanum leaf possesses significant anti-hyperglycaemic activity and encourages conventional use in the treatment of diabetes mellitus under the experimental conditions exposed in this study.